2017
DOI: 10.18632/oncotarget.19130
|View full text |Cite
|
Sign up to set email alerts
|

Down regulation of lincRNA-p21 contributes to gastric cancer development through Hippo-independent activation of YAP

Abstract: Long intergenic non-coding RNA p21 (lincRNA-p21), known as the direct transcriptional target of p53, was found down-regulated in several human solid tumors. However, little is known about the role of lincRNA-p21 in gastric cancer. The expression levels of lincRNA-p21 in tissue samples and cell lines were detected by qRT-PCR. MGC-803 and MKN-45 cells were transfected with siRNAs targeting lincRNA-p21 or control siRNAs to determine the effect of reduced lincRNA-p21 expression on tumorigenesis. We also overexpres… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
22
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 28 publications
(22 citation statements)
references
References 37 publications
0
22
0
Order By: Relevance
“…72 Consistently, its depletion in gastric cancer promotes EMT phenotypic changes in cells, and these changes are also seen at the transcriptome level. 73 79 Likewise, the overexpression of PVT1 resulted in an increase of Snail and ZEB1 expression in pancreatic cancer (Figure 2). 80…”
Section: Tumor Driversmentioning
confidence: 88%
“…72 Consistently, its depletion in gastric cancer promotes EMT phenotypic changes in cells, and these changes are also seen at the transcriptome level. 73 79 Likewise, the overexpression of PVT1 resulted in an increase of Snail and ZEB1 expression in pancreatic cancer (Figure 2). 80…”
Section: Tumor Driversmentioning
confidence: 88%
“…Some research have reported LncRNAs had involvement in the adjustment of EMT process of several cancer types. For example, knockdown of lincRNA-p21 promoted EMT of gastric cancer cells, but overexpression of lincRNA-p21 exerted opposite effects [29]. LincHOTAIR indirectly inhibited miR-7 to reverse the EMT process of breast cancer stem cells [30].…”
Section: Discussionmentioning
confidence: 99%
“…With regard to the function of MALAT1 in specific cells, the present study hypothesized that an interaction between MALAT1 and p53 exists in colorectal neoplasms. Previous studies have assessed the expression of lincRNA-p21 with various types of cancer (18,35,36). However, few studies report the influence of lincRNa-p21 on CRC.…”
Section: Lncrna-rormentioning
confidence: 99%